Respostas
respondido por:
1
resolução!
fração com denominadores iguais
= 15/12 + 8/12 - 11/12
= 15 + 8 - 11/12
= 12/12
= 1
gabriela7822:
eiii pode me ajudar???
a5 = a1 + 4r
4r = a5 - a1
4r = 5 - (- 7)
4r = 5 + 7
4r = 12
r = 12/4
r = 3
Agora, usando a fórmula do termo geral:
an = a1 + (n - 1).r
an = - 7 + (n - 1).3
an = - 7 + 3n - 3
an = 3n - 10
Resposta: 3n - 10
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás